Solve for u 5u+3=3(u-5)

Math
5u+3=3(u-5)
Simplify 3(u-5).
Tap for more steps…
Apply the distributive property.
5u+3=3u+3⋅-5
Multiply 3 by -5.
5u+3=3u-15
5u+3=3u-15
Move all terms containing u to the left side of the equation.
Tap for more steps…
Subtract 3u from both sides of the equation.
5u+3-3u=-15
Subtract 3u from 5u.
2u+3=-15
2u+3=-15
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
2u=-15-3
Subtract 3 from -15.
2u=-18
2u=-18
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2u=-18 by 2.
2u2=-182
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2u2=-182
Divide u by 1.
u=-182
u=-182
Divide -18 by 2.
u=-9
u=-9
Solve for u 5u+3=3(u-5)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top